2014
DOI: 10.1016/j.neuroscience.2014.03.041
|View full text |Cite
|
Sign up to set email alerts
|

Cortical involvement in the StartReact effect

Abstract: The rapid release of prepared movements by a loud acoustic stimulus capable of eliciting a startle response has been termed the StartReact effect (Valls-Solé et al., 1999), and premotor reaction times (PMTs) of <70 ms are often observed. Two explanations have been given for these short latency responses. The subcortical storage and triggering hypothesis suggests movements that can be prepared in advance of a “go” signal are stored and triggered from subcortical areas by a startling acoustic stimulus (SAS) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
36
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 61 publications
7
36
2
Order By: Relevance
“…Together with the findings in Stevenson et al (2014), the observations we have made here reveal a good deal of similarity between speech plans and other SASinduced (e.g., upper limb) movements. In SAS-induced speech, overall trajectories for a prepared response are generally maintained, whether relating to vowel formants, pitch, or lip movements.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Together with the findings in Stevenson et al (2014), the observations we have made here reveal a good deal of similarity between speech plans and other SASinduced (e.g., upper limb) movements. In SAS-induced speech, overall trajectories for a prepared response are generally maintained, whether relating to vowel formants, pitch, or lip movements.…”
Section: Discussionsupporting
confidence: 81%
“…Except as described here, apparatus and procedures for the present experiment were exactly as described for experiment 2 in Stevenson et al (2014).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent transcranial magnetic stimulation (TMS) studies show that the StartReact effect may not be limited to subcortically stored programs, but can also be observed in cortically dependent processes (Alibiglou and MacKinnon, 2012; Stevenson et al, 2014). These studies found that, when a cortical silent period was induced by applying TMS to motor cortex, the StartReact response was delayed in startle trials.…”
mentioning
confidence: 99%